Behavioral Intervention on with Trichotillomania. (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
The aim of this study wasaimed to analyze functionally the problem behavior of the self-pulling of thestrands of hair in of an individualperson diagnosed with trichotillomania, usingthrough habit reversal procedure. The participant was a young maiden of 21- year olds unmarried woman; a college student who had been receivingwas in medical and drugpharmacological treatment since the age of 12. To demonstrate the experimental control of the procedures, were used to design Reversal-Replication design was employed, using the ABAB format, followed by with follow-up. The intervention program was effective in reducing the behavior of pulling out the strands of hairs, and this that remained the case in the follow-up.
Keywords: Functional analysis; Therapeutic intervention; Habit reversal